Critical Synthesis Package: Physician Readiness to Manage Intimate Partner Violence (PREMIS) - Annalucia Bays; Kathleen Ingram (Association of American Medical Colleges, 2015)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and application to health sciences education for the Physician Readiness to Manage Intimate Partner Violence (PREMIS), and (2) a copy of the PREMIS instrument and PREMIS Toolkit developed by John Harris, MD and Lynn Short, PhD, MPH. The PREMIS is a 67-item, comprehensive measure assessing physician readiness to manage intimate partner violence (IPV). The measure is multi-faceted and contains four sections: Background (perceived preparation and knowledge), Knowledge (actual knowledge), Opinions (attitudes and beliefs), and Practice Issues (physician/office behaviors). According to developers, items are consistent with the theoretical literature on IPV. The measure takes 15-35 minutes to complete and can be administered in paper− and web-based formats. Self-report responses are made through Likert-type scale, true/false, multiple-choice, and open response options. Several studies provide tentative evidence for construct validity, predictive validity, external validity, internal consistency, and temporal stability. The PREMIS has been adapted and validated for use with multiple health care professional populations and translated into several languages. Furthermore, the PREMIS could have a number of research and educational uses, including identifying populations requiring IPV training, evaluating IPV curricula, and assessing IPV constructs pre− and posttest. However, further evaluation of the PREMIS and variations thereof is needed to assess the stability of its psychometric properties (as the development sample size was inadequate to conduct factor analyses), several studies report conflicting evidence of subscale reliability, and no studies have assessed convergent validity.